The Relationships of Work Environment, Compensation, And Organizational Commitments on Employee Retention - I Kadek Rama Dwi Saputra; I Gede Riana (Penerbit Kemala Indonesia, 2021)
Employee retention is an organization's effort to retain its potential employees. In this study aimed to analyse the effect of non-physical work environment, compensation, and organizational commitment on potential employee retention. Here, the sample population of this study taken from housekeeping and room service section totalling 60 employees over Tjampuhan Hotel, Gianyar, Bali. The determination of sample collection is use saturated sampling method with interview and questionnaire from 60 employees. Furthermore, in the processing data we analyse using descriptive and multiple linear regression analysis, respectively. The results show non-physical work environment doesn’t significant effect on employee retention, compensation, and organizational commitment. However, partially have a positive and significant effect on employee retention. This indicates that employee retention is not influenced by the non-physical work environment. However, it can be explained that the good result is captured according to the compensation received and organizational commitment with increase employee retention. Thus, the employees are retaining their membership in the organization.